Knowledge, Politics and Decoloniality - Biondi, Paolo (Soft Power, 2024)
On Decoloniality is the updated introduction to decolonial thought, written together by two of its key exponents, Walter D. Mignolo and Catherine E. Walsh. When we speak of decolonial thought, we are referring to the work of a group of scholars —including among the most renowned also Santiago Castro-Gómez, Ramón Grosfoguel, Enrique Dussel, Edgardo Lander and Boaventura de Sousa Santos— that starting from the mid 1990s finds a common ground of research around the work of the Peruvian sociologist Aníbal Quijano (e.g. 2007, 2010) from one side, and, from the other, in the contributions of Latin-American and Afro-Caribbean intellectuals like Paulo Freire, Frantz Fa- non, and Aimée Cesaire (Restrepo & Roja 2010).